Enhancement of Photovoltaic Current through Dark States in Donor‐Acceptor Pairs of Tungsten‐Based Transition Metal Di‐Chalcogenides. (31st March 2021) - Roy, Sayan; Hu, Zixuan; Kais, Sabre; Bermel, Peter
Abstract: As several photovoltaic materials experimentally approach the Shockley–Queisser limit, there has been a growing interest in unconventional materials and approaches with the potential to cross this efficiency barrier. One such candidate is dark state protection induced by the dipole–dipole interaction between molecular excited states. This phenomenon has been shown to significantly reduce carrier recombination rate and enhance photon‐to‐current conversion, in elementary models consisting of few interacting chromophore centers. Atomically thin 2D transition metal di‐chalcogenides (TMDCs) have shown great potential for use as ultra‐thin photovoltaic materials in solar cells due to their favorable photon absorption and electronic transport properties. TMDC alloys exhibit tunable direct bandgaps and significant dipole moments. In this work, the dark state protection mechanism has been introduced to a TMDC based photovoltaic system with pure tungsten diselenide (WSe2 ) as the acceptor material and the TMDC alloy tungsten sulfo‐selenide (WSeS) as the donor material. Our numerical model demonstrates the first application of the dark state protection mechanism to a photovoltaic material with a photon current enhancement of up to 35% and an ideal photon‐to‐current efficiency exceeding the Shockley–Queisser limit. Abstract : A transition metal di‐chalcogenide (TMDC) based donor–acceptor photovoltaic model with dark state protection is demonstrated, where the dark state protection mechanism reduces carrier recombination and enhances photon‐to‐electron conversion due to dipole–dipole interactions. This model has a significantly higher output current compared to standard heterojunction solar cells, with a potential to exhibit efficiencies above conventional limits.